Development of A Virtual Laboratory Based on Augmented Reality (AR) for Series Circuit Material at SMPN 9 Kota Kediri - Syafruddin, Aldy Iqbal; Inzagi, Nadhea Aurel Zalfanisa; Fatmaningsih, Lidiya; Nurazmi; Daud, Dalila Haji (Islamic Journal of Integrated Science Education (IJISE), 2025)
This study aims to develop and evaluate the practicality and effectiveness of a virtual laboratory based on Augmented Reality (AR) for teaching series circuits to 9th-grade students at SMPN 9 Kota Kediri. The media is designed to address students' difficulties in understanding concepts of current, voltage, and resistance, which often result from teacher-centered learning methods. The research method used in this study is research and development with ADDIE design are analysis, design, development, implementation, and evaluation. The validity of the media was assessed by experts, and its effectiveness was evaluated through pre-tests, post-tests, and questionnaires. AR technology enables a more interactive and visual learning experience without the limitations of physical laboratory tools. The design and development of the Augmented Reality (AR)-based virtual laboratory learning media effectively improve the learning outcomes and motivation of ninth-grade students at SMPN 9 Kota Kediri, particularly on the topic of series electric circuits.